Local microwave heating - Бондаренко, И. Н.; Бендеберя, Г. Н.; Горбенко, Е. А. (My University, 2019)
Experimental studies of the posibilities of practical implementation of local microwave heating technology have been carried out.
Keywords: microwave; high-local; heating; technology; coaxial probe; micromodifier